Occurrence of Halotolerant algae in Shallow Saline Water (bogs), Distributed in Basrah City, Iraq - Al-Mousawi, Nida J. (University of Thi-Qar Journal of Science, 2019)
A study was made on the halotolerant algae occurance in (32) area of shallow saline water (bogs) distributed in Basrah city south of Iraq in Jouly 2011. A total of (24) taxa were Identified. Algal were collected and maintained as unialgal culture of the locally isolated such as cyanobacterium Arthrospira (spirulina) platensis and micro green alga Dunaliella salina.The salinity of water were around from (2.5-60.5)‰. According to the results of a total hardness (Lind, 1979) recent data revealed that the total hardness (600-144000)mg CaCO3/L of studied shallow saline water were very hard.